Learning from one another - global systems consultancy - Weiß, Reinhold [Verfasser] (My University, 2009)
"Professor Reinhold Weiß, research director of the BIBB (Federal Institute for Vocational Education and Training), highlights the varied activities of the involvement of BIBB in international cooperation in vocational education and training. Core of the BIBB consultancy is the development of demand-oriented concepts for vocational education and training in other countries."(BIBB-Doku)
Keywords: I 1.1 Systemberatung; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Berufsbildung; Internationale Zusammenarbeit; Bildungsdienstleistung; Bundesinstitut für Berufsbildung